2020
DOI: 10.18502/acta.v57i11.3280
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Clinical Characteristics of Rotavirus and Norovirus Infections in Hospitalized Children Less Than 5 Years of Age With Acute Gastroenteritis in Tehran, Iran

Abstract: Acute gastroenteritis is one of the most important causes of death in children in developing countries which cause by different enteropathogens, including bacteria, viruses, and parasites. Among these, most of the acute gastroenteritis in children are caused by viral infections mainly by rotavirus and norovirus. This study aimed to study the epidemiological and clinical status of acute gastroenteritis resulting from rotavirus and norovirus in children between June 2015 and June 2016 in Iran. A total of 211 sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The VP8* sequences were obtained from 20 to 88 rotavirus strains in the present and previous 64,65 studies, respectively. As depicted in Figure 1A, The phylogenetic tree showed that all rotavirus strains from Iran belonged to P[II] genogroup, and also indicated that the most common detected rotaviruses belonged to P [8] genotype (n = 102; 94.4%), while the remaining belonged to P [4] (n = 3; 2.8%) and P [6] (n = 3; 2.8%) genotypes (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…The VP8* sequences were obtained from 20 to 88 rotavirus strains in the present and previous 64,65 studies, respectively. As depicted in Figure 1A, The phylogenetic tree showed that all rotavirus strains from Iran belonged to P[II] genogroup, and also indicated that the most common detected rotaviruses belonged to P [8] genotype (n = 102; 94.4%), while the remaining belonged to P [4] (n = 3; 2.8%) and P [6] (n = 3; 2.8%) genotypes (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…and Eftekhari et al. on children under 5 years of age in Iran, the prevalence of norovirus was 17.5% and 20.0%, respectively [ 33 , 34 ]. This virus is an important pathogen in immunocompromised patients where cases of norovirus-associated death have been reported in this group of patients, including in non-Hodgkin lymphoma [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhea in Uganda is still ranked among the top 10 causes of morbidity, mainly because it is highly contagious and associated with severe dehydration leading to shock and multiorgan failure [ 13 , 14 ]. Studies carried out at Mulago National Hospital in 2010 and 2012 respectively found a pre-rotavirus vaccination prevalence of 45.4% among children aged 3–59 months [ 14 ] and 32.8% among children under 5 years [ 15 ].…”
Section: Introductionmentioning
confidence: 99%